Breaking up with Elsevier - Bijsterbosch, Janine; Aspaas, Per Pippin (Open Science Talk, 2023)
Janine Bijsterbosch, member of the editorial team of Imaging Neuroscience, informs about their recent break with publishing giant Elsevier. Collectively, the entire team of editors of Neuroimage left Elsevier to form a new journal, Imaging Neuroscience, at MIT Press. While Neuroimage already was an open access journal, it charged 3,450 dollars in Article Processing Charge (APC). At MIT Press, Imaging Neuroscience will charge 1,600 dollars in APC, with waivers for authors from low- and middle-income countries. Bijsterbosch explains why the editors collectively resigned from Neuroimage and what they hope to achieve with the move to a less costly model. At the time when the editors left Neuroimage, they published around 1,000 peer reviewed articles per year, with an Impact Factor of 7.4. With the non-profit Imaging Neuroscience, they hope to bring authors and peer reviewers with them in their effort to build the (new) leading publishing outlet for researchers in the field. The reception has been quite positive and large amounts of manuscripts are already being submitted to the new journal. Besides the economics and ethics of sustainability, Bijsterbosch is concerned with other aspects of open and transparent science, such as Open Code and Open Data. She sees Imaging Neuroscience as a player in this field as well, with Author’s Instructions including statements about the sharing of code and data whenever possible.